A Probe Into the Psychological Mechanism of Generation Z College Students Using Network Buzzwords in the Internet Era - Dong, Dandan (Frontiers in Psychology, 2021)
Network buzzwords are ubiquitous in the internet era. To explore the psychology of college students using network buzzwords, the development trend and characteristics of network buzzwords are analyzed first. A questionnaire survey is performed to learn how college students use network buzzwords currently; then, the obtained data are analyzed and discussed. Results demonstrate that 81.59% of college students can understand what the buzzwords mean. As for psychological factors, the average score of the identity dimension is the highest, and the average score of social support is the lowest. Among the behavioral factors, the communication factor scores the highest. Regarding the overall psychological and behavioral factors, boys score generally higher than girls, and science and engineering students score higher than those majoring in literature, history, and art. Students of higher grades score lower than those of the lower grades regarding using network buzzwords in communication and entertainment activities. The psychological mechanism of Generation Z college students using network buzzwords has been explored, which can provide scientific and practical reference materials for subsequent analysis and research on college students’ online behaviors and is also of great significance for college students’ internet education.